BAP1 Tumour Predisposition Syndrome Due to Whole BAP1 Gene Deletion - Dinusha Pandithan; Sonja Klebe; Grace McKavanagh; Lesley Rawlings; Sui Yu; Jillian Nicholl; Nicola Poplawski (Case Reports in Genetics)
BRCA-1-associated protein-1 (BAP1) tumour predisposition syndrome (BAP1-TPDS) is a dominant hereditary cancer syndrome. The full spectrum of associated malignancies is yet to be fully characterised. We detail the phenotypic features of the first reported family with a whole BAP1 gene deletion. This report also adds to the emerging evidence that the rhabdoid subtype of meningioma is a part of the clinical spectrum of this tumour predisposition syndrome.